Electromotive Forces on Multitier Instruments (EFoMI): Development to measure student misconception with Rasch - Eliya, Meisy; Purwianingsih, Widi; Supriatna, Asep; Samsudin, Achmad; Aminudin, Adam Hadiana; Mardiana, Mardiana (Journal of Environment and Sustainability Education, 2024)
This research aims to develop Electromotive Forces on Multitier Instruments (EFoMI) in measuring student misconceptions. Method: This development research uses 4D design. Participants in this research were 19 students (10 Females and 9 Males) in one of the Bandung junior high schools. The instruments used are those developed in this research. The Rasch analysis was used to identify the feasibility of EFoMI using WINSTEPS 4.4.5 software which had previously been included in the conceptual categories of Sound Understanding (SU), Partial Positive (PP), Partial Negative (PN), No Understanding (NU), Misconception (MC), and No Coding (NC). Meanwhile, VOSviewer analysis was carried out to look for research trends related to misconceptions. Results: The results show the construct validity and fit statistics which meet all criteria. the reliability of EFoMI, namely 0.82, is in the Very Good category. The difficulty level of EFoMI is evenly distributed, the discrimination in the Very Good category, and no gender bias was detected from EFoMI. The distribution of students' conceptions includes SU= 12%, PP= 4%, PN= 45%, NU= 7%, MC= 27%, and NC=4%. These results have several implications in the field of education. An example is EFoMI's success in identifying student misconceptions, thus it can be an alternative for teachers in developing or identifying student misconceptions. Then, by knowing students' initial conceptions, teachers can develop learning tools that are more focused on student misconceptions and based on data. Likewise, to develop or use teaching materials more effectively by knowing the areas where students often experience misconceptions.